When the Topic Is Racism: Research and Advocacy with A Community Coalition - Haluza-DeLay, Randolph (Social justice, 2003)
Part of a special issue on applied research and social justice. An account of a community-led study on racism in Thunder Bay, Ontario, Canada is presented. A number of issues raised by the project that relate to the role of research consultants working in social justice initiatives at community level are discussed—research questions, research methods, the intersection of theory and practical value, research as knowledge production, research as disguised activism, and research as divisive in the community.